Studies on the genus Atriplex (Chenopodiaceae) in Italy. VI. Names by Michele Tenore: Atripelx axillaris, A. diffusa, and A. polysperma - Iamonico, Duilio; P. Sukhorukov, Alexander (Hacquetia, 2015)
The typification of the names Atriplex axillaris, A. polysperma (both names are synonyms of A. rosea L.), and A. diffusa (synonymized with A. tatarica here) is discussed. Specimens from Tenore’s collection (NAP) and from De Candolle’s collection (G-DC) are respectively designated as the lectotypes of A. diffusa and A. axillaris, while one collection from NAP is designated as the neotype for the name A. polysperma.